Gambaran Pengetahuan Ibu Hamil Tentang Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) Berdasarkan Karakteristik di Desa Cibogo Kecamatan Lembang Kabupaten Bandung Barat - Lubina V; Tenang Juvita Sitepu (STIKes Karsa Husada Garut, 2015)
Every an hour, two mothers are die durring giving birth. The maternal mortality rate in Indonesia is still high. Many families prefer a traditional birth attendant for various reasons. But if complications ocured, the traditional birth attendants may not be able to overcome. One of the efforts to bring it down that the delivery planning program and Complications Prevention program (P4K). The purpose of this study was to describe the knowledge of pregnant women about P4K based on the characteristics in the Village District Lembang Cibogo West Bandung regency. This research method was descriptive. The population in this study were pregnant women in the Cibogo village, sampling technique in this research was total sampling with total sample of 79 respondents. The results showed that most of respondents (58.2%) have less knowledge about P4K. Based on the characteristics, respondents who have less knowledge aged <20 years or> 35 years (70.3%), almost an of respondentsnhave educated from a school (84.2%), most of them not work (67.3%) and Sundanese have (55.9%). Conclusion the lack of knowledge about the program P4K pregnant women due to lack of information received by the mother. Improving knowledge of pregnant mothers and families about P4K is necessary to prevent maternal mortality and childbirth, this matter can be done through the socialization by Posyandu health health volunter and community leaders to pregnant women and family style.